Does the stabilization of the calcaneocuboid joint with Steinmann pin in Evans osteotomy affect its incidence of arthritis?. (December 2021) - Attia, Elsayed; Heldt, Brett; Roepe, Isaiah G.; Shenava, Vinitha R.; Hill, Jaclyn F.
Highlights: Evans osteotomy is currently the most used surgical treatment option for pediatric pes planovalgus. Calcaneocuboid joint arthritis is a serious complication of this procedure, yet its pathogenesis is not fully understood. Calcaneocuboid subluxation, graft size, patient age at surgery, and stabilization of the joint post-operatively are possible risk factors. Better understanding of the mechanism of this complication is warranted for better functional outcomes post-operatively. Abstract: Purpose: This study aims to determine the effect of retaining a Steinmann pin in the calcaneocuboid joint on its rates of arthritis following Evans calcaneal osteotomy lengthening procedure. The study hypothesized that leaving the pin across the calcaneocuboid joint post-operatively would lead to higher rates of arthritis. Methods: This is a retrospective review of patients under 18 years of age who underwent Evans osteotomy at our hospital from January 2015 to May 2020. The Patients were stratified into 2 groups: Group 1 (pin was left post-operatively across the joint and removed on follow-up) and Group 2 (pin was removed during surgery). Demographic data were recorded, including age, sex, and body mass index. Calcaneocuboid arthritis was determined by radiographic imaging at least one-year follow-up. Time to pin removal, size of the pin and graft, and subluxation were analyzed as possible risk factors for arthritis. Odds ratios (OR) and corresponding 95% confidence intervals (CI) were estimated. Results: 39 patients were included in the study: 24 patients had the pin removed post-operatively, and 15 had the pin removed intra-operatively. There were no significant differences between the 2 groups regarding body mass index, age, sex, or laterality. Calcaneocuboid arthritis rates were significantly higher in the Group 1 than Group 2 (12(50%) vs. 2(13.3%), respectively; p = 0.02). On multivariate regression, both age (OR, 1.305 [95%CI: 1.009−1.696]; p = 0.044) and leaving the pin in the joint postoperatively (OR, 7.661 [95%CI: 1.208−48.570]; p = 0.031) were found as risk factors for arthritis at follow-up. The mean time to pin removal, the size of the pin, and the size of the graft were not found to be significant predictors of arthritis (p > 0.05). Conclusions: This study shows that leaving the Steinmann pin in the calcaneocuboid joint in children post-operatively is associated with an increased risk of developing early radiographic signs of calcaneocuboid joint arthritis.